Invasive meningococcal disease epidemiology and characterization of Neisseria meningitidis serogroups, sequence types, and clones; implication for use of meningococcal vaccines. Issue 1 (2nd January 2019) - Stein-Zamir, Chen; Shoob, Hanna; Abramson, Nitza; Block, Colin; Keller, Natan; Jaffe, Joseph; Valinsky, Lea
ABSTRACT: Background and aims : Neisseria meningitidis ( N. meningitidis ) is a Gram-negative bacterium that can cause life-threatening invasive infections referred to as invasive meningococcal disease (IMD). In the last decade the incidence of IMD in Israel is about 1/100, 000 population annually. We aimed to describe the epidemiology of IMD in Israel combining epidemiological data and characterization of N. meningitidis isolates. Methods : Invasive infection caused by N. meningitidis is a notifiable disease in Israel. Data were collected by epidemiological investigations and control measures were employed. Laboratory work-up included serogrouping, N. meningitides molecular characterization and whole-genome sequencing. Results : During 1998–2017, 1349 cases of IMD were notified in Israel (mean annual incidence rate 0.94/100, 000). The peak incidence rates were observed in infants under 1 year of age (10.9/100, 000). Case fatality rate was 9.7%. The majority of the N. meningitidis isolates were of serogroup B (67.9%). During 2007–2017, three clonal complexes (CC) 32, 41/44 and 23 (hyper-invasive clonal complexes) were the leading CC (61%). CC32 was the leading CC causing meningococcemia and mortality. In 2017, 35 isolates were tested for 4CMenB antigens variants; of the serogroup B isolates tested 46.7% showed a match to one or more antigens (fHbp or PorA:VR1), most were ST32 (CC32). Conclusions : Preliminary analysis based on limited number of samples suggests that the 4CMenB coverage would be about half the strains; further research is necessary. Integration of clinical, epidemiological and laboratory data is essential to support decision-making on the introduction of the novel MENB vaccines in Israel.